A systematic review about Streptococcus Pneumoniae serotype distribution in children in mainland of China before the PCV13 was licensed - Shuang Lyu; Hui-li Hu; Yong-hong Yang; Kai-hu Yao (Expert Review of Vaccines, 2017)
Introduction: Streptococcus pneumoniae (S. pneumoniae) is a major pathogen of infectious diseases in children. Surveillance of the distribution of pneumococcus serotypes is important for immunization strategies of pneumococcal polysaccharide conjugate vaccines (PCVs). Areas covered: This article is a systematic review of studies conducted from 2006 to 2016 that document serotypes of S. pneumoniae isolated from children less than 14 years old in the mainland of China. A total of 40 studies were included in this review. Serotypes 19F, 19A, 23F, 14 and 6B were the most common. Serotype prevalence and percentage varied by region and associated strains. The serotype coverage rate of PCV13 was higher than that of PCV10 due to the prevalence of serotype 19A, and there were no significant difference between the coverage rate of PCV13 and PPSV23. Expert commentary: To prevent Chinese children from S. pneumoniae infection, it is necessary for the universal immunization of PCV13 or develop new vaccines that include all the prevalent serotypes in China.